Effect of biomimetic mineralization on enamel and dentin: A Raman and EDX analysis - Guentsch, Arndt; Fahmy, Mina D.; Wehrle, Constanze; Nietzsche, Sandor; Popp, Juergen; Watts, David C.; Kranz, Stefan; Krafft, Christoph; Sigusch, Bernd W. (Dental Materials, 2019)
Objective: To investigate the effect of an experimental biomimetic mineralization kit (BIMIN) on the chemical composition and crystallinity of caries-free enamel and dentin samples in vitro. Methods: Enamel and dentin samples from 20 human teeth (10 for enamel; 10 for dentin) were divided into a control group without treatment and test samples with BIMIN treatment. Quantitative analysis of tissue penetration of fluoride, phosphate, and calcium was performed using energy-dispersive X-ray spectroscopy (EDX). Mineralization depth was measured by Raman spectroscopy probing the symmetric valence vibration near 960 cm−1 as a marker for crystallinity. EDX data was statistically analyzed using a paired t-test and Raman data was analyzed using the Student's t-test. Results: EDX analysis demonstrated a penetration depth of fluoride of 4.10 ± 3.32 μm in enamel and 4.31 ± 2.67 μm in dentin. Calcium infiltrated into enamel 2.65 ± 0.64 μm and into dentin 5.58 ± 1.63 μm, while the penetration depths for phosphate were 4.83 ± 2.81 μm for enamel and 6.75 ± 3.25 μm for dentin. Further, up to 25 μm of a newly mineralized enamel-like layer was observed on the surface of the samples. Raman concentration curves demonstrated an increased degree of mineralization up to 5–10 μm into the dentin and enamel samples. Significance: Biomimetic mineralization of enamel and dentin samples resulted in an increase of mineralization and a penetration of fluoride into enamel and dentin.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Biomimetic; Dentin; EDX; Enamel; Mineralization; Raman